(untitled) (Medico Legal Update, 2020)
Backgrounds : This study evaluated the antimicrobial properties of a newly prepared, cement-based capping material and biopolymer (chitosan) with Mineral Trioxide Aggrigate MTA and Biodentine. Method: The antibacterial effects of a set of specimens against Streptococcus mutans, Rothia dentocariosa, and Enterococcus faecalis were evaluated by agar diffusion tests. Thirty disc-shaped specimens (10 of each type of materials; 6 mm in diameter × 2 mm in thickness) were prepared. One specimen for each material was placed on each agar plate, and the plates incubated for 24 h. After incubation, the diameter of the inhibition zone was calculated at three different points and averaged. Results: Statistically significant differences were found among new calcium-based capping material, MTA, and Biodentine. An ANOVA test was used to evaluate the effect of materials against each type of bacteria. This revealed that the inhibition zones produced by the new cement based capping material mixture were statistically significantly larger than those produced by the other materials. Conclusions: Within the limitations of the experimental methods employed in the present study, the cement-based capping material prepared from egg shells and the biopolymer chitosan has better antimicrobial properties than Biodentine and MTA.